Citrix XenServer 6.0 administration essential guide : deploy and manage XenServer in your enterprise to create, integrate, manage, and automate a virtual datacenter quickly and easily /: deploy and manage XenServer in your enterprise to create, integrate, manage, and automate a virtual datacenter quickly and easily. (2012) - Tosatto, Daniele
No abstract available